Die Kerkbode as primêre bron vir kerkhistoriese navorsing 1860-1883 - J.J. Lubbe (Acta Theologica)
One of the primary sources of research into the history of the Dutch Reformed Church, is Die Kerkbode, official organ of this church. In this article the author stresses the need for a contextual and theological interpretation of the source. To serve that purpose, three successive periods in the history of Die Kerkbode were selected. Some of the major theological trends and developments which have been reflected in it, will be discussed. It does not try to summarize the content of Die Kerkbode in this particular period, but rather focuses on the story of this source itself in an effort to define its character and selfconcept. The article concludes that it is possible to get a proper picture of the spirit of the Dutch Reformed Church in that time, bearing in mind that it is a picture through the eyes of those who were closely involved with Die Kerkbode.